Current views on the use of long-acting anticholinergic drug tiotropium in the treatment of bronchial asthma among children - E. V. Churyukina (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
Despite treatment of bronchial asthma, in accordance with current recommendations, inhaled corticosteroids as monotherapy or in combination with long-acting β2 agonists, at least 40% of patients fail to achieve disease control. The long-acting anticholinergic drug Tiotropium (through a liquid inhaler Respimat) is recommended for use in adults and children over S years of age by experts from GINA, the Russian respiratory society and the Pediatric respiratory society as an additional strategy for achieving bronchial asthma control. The article highlights the pharmacological properties of Tiotropium and its mechanism of action in asthma. The results of the author's own research on the use of Tiotropium in children S-11 years of age with moderate and severe bronchial asthma in real clinical practice are presented.